2018
DOI: 10.3389/fgene.2018.00388
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Vitamin B6, Diabetes and Cancer

Abstract: Pyridoxal 5′-phosphate (PLP), the active form of vitamin B6, works as cofactor in numerous enzymatic reactions and it behaves as antioxidant molecule. PLP deficiency has been associated to many human pathologies including cancer and diabetes and the mechanism behind this connection is now becoming clearer. Inadequate intake of this vitamin increases the risk of many cancers; furthermore, PLP deprivation impairs insulin secretion in rats, whereas PLP supplementation prevents diabetic complications and improves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 66 publications
1
46
0
Order By: Relevance
“…This is relevant considering that although in developed countries B6 deficiency caused by dietary insufficiency is rare, in contrast, low B6 status (<20nmol/L) is common in the population and affects smokers, contraceptive users, alcoholists, patients suffering coeliac disease or diabetes and pregnant women. In addition, a decreased PLP dosage can be produced by drugs that reduce its availability (di Salvo et al, ; Merigliano, Mascolo, Burla et al, ). Accordingly with our results the importance of a tight PLP dosage regulation has emerged also in humans from a recent study by di Salvo et al () which demonstrated that the 347G>A missense mutation in the PNPO human gene although produces only a slight reduction of catalytic efficiency can, however, cause epilepsy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is relevant considering that although in developed countries B6 deficiency caused by dietary insufficiency is rare, in contrast, low B6 status (<20nmol/L) is common in the population and affects smokers, contraceptive users, alcoholists, patients suffering coeliac disease or diabetes and pregnant women. In addition, a decreased PLP dosage can be produced by drugs that reduce its availability (di Salvo et al, ; Merigliano, Mascolo, Burla et al, ). Accordingly with our results the importance of a tight PLP dosage regulation has emerged also in humans from a recent study by di Salvo et al () which demonstrated that the 347G>A missense mutation in the PNPO human gene although produces only a slight reduction of catalytic efficiency can, however, cause epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition PLP acts as a modulator of steroid hormone receptor‐mediated gene expression (di Salvo, Contestabile, & Safo, ) and it is able to quench reactive oxygen species (ROS) and advanced glycation end products (AGEs) (Bilski, Li, Ehrenshaft, Daub, & Chignell, ). Based on its wide range of functions it is not surprising that PLP is beneficial for many human diseases such as schizophrenia, epilepsy, Alzheimer's disease, Parkinson's disease, malaria, diabetes, and cancer (di Salvo, Safo, & Contestabile, ; Merigliano, Mascolo, Burla, Saggio, & Verni, ).…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, the present study focuses specifically on this form of vitamin B 6 to shed new light on one of the possible mechanisms underlying this inhibitory activity. The other two forms have also been reported to show antioxidant activity [66,67] and the aforementioned study on the ROS trapping ability of PN [28] shows that it shares some of the preferred reaction sites with PM (namely, the phenol group, the methylene moieties and the aromatic carbons adjacent to the pyridine nitrogen). Since PLP also displays all these structural elements, it is plausible that it also scavenges ROS by similar mechanisms.…”
Section: Discussionmentioning
confidence: 96%
“…This reveals that HNC patients require nutritional intervention with a special attention to the quantification of food intake in order to estimate possible deficits and achieve adequate levels of macro-and micronutrients through prophylactic ONS prescription. Previous studies have highlighted the importance of vitamin B6 as a protective factor against the development of cancer [40], antioxidant effects [41], and increased immune response [42].…”
Section: Discussionmentioning
confidence: 99%